IDENTIFICATION OF VARIOUS PROBLEMS ON BREAST CANCER PATIENT IN YOUNG WOMEN - Devy Ade Kusyanti (Universitas Udayana, 2013)
Breast cancer is a cancer that forms in tissue of the breast such as lactiferous duct, lobules and nipple. Around hundreds of breast cancer cases in the world, less than 0,1% occur in young women less 20 years old, 1,9% on 20 and 34 years old, and 10,6% between 35 and 44 years old. Various problems of breast cancer patients in young women that genetics issues, diagnostic issues, management issues, fertility issues, and quality of life and psychosocial issues are a particular challenge that need a special attention and solution in future. A multidisciplinary team is needed as a solution on the future.